Cheetah conservation in the Horn of Africa – notes and thoughts in the light of field experiences - Balogh, Balázs (Afrika Tanulmányok / Hungarian Journal of African Studies, 2024)
The future of many of the emblematic species of the African continent is facing enormous challenges in our modern, tumultuous world. Yet, there is a growing number of conservation participants whose perseverance and dedication show an excellent example for the coming generations. This article intends to present the cheetah as a flagship species of the African landscape, to provide a general overview of its conservation, and to introduce the work of the Cheetah Conservation Fund (CCF), the major organization committed to protecting the species. It aims to do so based on personal field experiences in CCF’s facility in Somaliland, putting the conservation effort in the political-economic context of the Horn of Africa